Comprehensive efficiency evaluation of wastewater treatment plants in northeast Qinghai–Tibet Plateau using slack–based data envelopment analysis. (15th October 2022) - Feng, Zhaohui; Liu, Xiaojie; Wang, Lingqing; Wang, Yong; Yang, Jun; Wang, Yazhu; Huan, Yizhong; Liang, Tao; Yu, Qiming Jimmy
Abstract: Comprehensive efficiency analysis of wastewater treatment plants (WWPTs) in the alpine region with harsh environment and poor techniques as well as managing experience could provide targeted and effective improvement evidences for local wastewater treatment industry and help to improve the water quality of downstream reaches. In this paper, slack–based data envelopment analysis (SBM–DEA) was adopted to assess the operating efficiencies of WWPTs in northeast Qinghai–Tibet Plateau (QTP). Results showed that the average efficiency score for all WWPTs was 0.608, and 32.5% of WWPTs were efficient. Some WWPTs had large improvement potentials in operating costs and pollutant removal rates. Lowering expenditures and promoting facility construction for WWPTs to overcome the climate difficulties and improve management level was necessary according to their improvement potentials. In addition, the relative importance of the quantitative influential factors to efficiencies scores calculated by random forest regression (RFR) indicated that design capacity and temperature were important quantitative factors affecting the performance of WWPTs. Furthermore, geographical location and design capacity also had significant influence on the comprehensive efficiency of WWPTs verified by Kruskal–Wallis test. Our results highlight the importance of facilities upgrading, scientific management for WWPTs. And the relative improvement suggestions on overcoming the high and cold environment should also be considered for the efficient operations of WWTPs as well as the protection the aquatic environment. Graphical abstract: Image 1 Highlights: Operating efficiency of WWPTs in the northeast QTP was evaluated by SBM–DEA. Some WWPTs had improvement potentials on saving cost and pollutant removal rates. Temperature and designed capacity were important factors in impacting efficiency. Lower altitude and higher temperature were more benefit for operation of WWPTs. Insulation, upgrading and reconstructing were necessary for WWPTs in QTP.